Discovery of information from the Internet service providers (ISPs): the position under the law in Malaysia and the United Kingdom - Mohamed, Duryana (UiTM, 2014)
Discovery of information is one of the methods used by the lawyers to gather information from the opposite parties before the case go for a full trial. The information to be discovered is subjected to either privileged or non-privileged information. This method is also used by the parties to find out Internet Protocol (IP) address of the subscribers and their details from their Internet Service Providers (ISPs). The issues are whether such discovery is allowed and how it is implemented in Malaysia and the United Kingdom. Are there any restraints or challenges to discovery against the ISPs? This paper will discuss the above issues by looking at the relevant laws and cases available in both countries. Keywords: Discovery, information, Internet Service Providers, laws, challenges